Understanding retention and metabolization of aroma compounds using an in vitro model of oral mucosa - Ployon, Sarah; Brulé, Marine; Andriot, Isabelle; Morzel, Martine; Canon, Francis (Food chemistry, 2020)
•Interactions between oral mucosa, saliva and aroma compounds were studied in vitro.•Mucosal cells can metabolize several aroma compounds thereby generating new compounds.•Release kinetic patterns are different depending on aroma hydrophobicity.•Mucosal pellicle impacts early release, particularly for a less hydrophobic aroma. The mechanism leading to aroma persistence during eating is not fully described. This study aims at better understanding the role of the oral mucosa in this phenomenon. Release of 14 volatile compounds from different chemical classes was studied after exposure to in vitro models of oral mucosa, at equilibrium by Gas-Chromatography-Flame Ionization Detection (GC-FID) and in dynamic conditions by Proton Transfer Reaction- Mass Spectrometry (PTR-MS). Measurements at equilibrium showed that mucosal hydration reduced the release of only two compounds, pentan-2-one and linalool (p < 0.05), and suggested that cells could metabolize aroma compounds from different chemical families (penta-2,3-dione, trans-2-hexen-1-al, ethyl hexanoate, nonan- and decan-2-one). Dynamic analyses for pentan-2-one and octan-2-one evidenced that the constituents of the mucosal pellicle influenced release kinetics differently depending on molecule hydrophobicity. This work suggests that mucosal cells can metabolize aroma compounds and that non-covalent interactions occur between aroma compounds and oral mucosa depending on aroma chemical structure.